Data from: Comparative analyses of plastid and AFLP data suggest different colonization history and asymmetric hybridisation between Betula pubescens and B. nana - Eidesen, Pernille Bronken; Alsos, Inger Greve; Brochmann, Christian (Zenodo, 2015)
Birches (Betula spp.) hybridize readily, confounding genetic signatures of refugial isolation and postglacial migration. We aimed to distinguish hybridization from range-shift processes in the two widespread and cold-adapted species B. nana and B. pubescens, previously shown to share a similarly east–west-structured variation in plastid DNA (pDNA). We sampled the two species throughout their ranges and included reference samples of five other Betula species and putative hybrids. We analysed 901 individual plants using mainly nuclear high-resolution markers (amplified fragment length polymorphisms; AFLPs); a subset of 64 plants was also sequenced for two pDNA regions. Whereas the pDNA variation as expected was largely shared between B. nana and B. pubescens, the two species were distinctly differentiated at AFLP loci. In B. nana, both the AFLP and pDNA results corroborated the former pDNA-based hypothesis that it expanded from at least two major refugia in Eurasia, one south of and one east of the North European ice sheets. In contrast, B. pubescens showed a striking lack of geographic structuring of its AFLP variation. We identified a weak but significant increase in nuclear (AFLP) gene flow from B. nana into B. pubescens with increasing latitude, suggesting hybridization has been most frequent at the postglacial expansion front of B. pubescens and that hybrids mainly backcrossed to B. pubescens. Incongruence between pDNA and AFLP variation in B. pubescens can be explained by efficient expansion from a single large refugium combined with leading-edge hybridization and plastid capture from B. nana during colonization of new territory already occupied by this more cold-tolerant species. AFLPmatrix_original_B_nana Binary AFLP matrix with 119 markers, 570 individuals of Betula nana and B. glandulosa generated by 3 primer combinations BN_BG_570_119.txt AFLPmatrix_orginal_Betula_pub_alle_332_155 Binary AFLP matrix with 155 markers, 332 individuals of mainly Betula pubescens, but also including reference species and ...